Modern Audit of Corporate Strategy of Selected Company - Burlacu, Andrei Daniel; Kupec, Václav; Písař, Přemysl, 1978-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2022)
The current global and economic environment is constantly changing and evolving, thus demanding constant and effective adaptability and innovation. The following bachelor’s thesis revolves around the process of auditing the corporate strategy of IB Cargo s.r.l., in order to discover and recommend possible areas of improvement. As IB Cargo is a company operating in the freight forwarding business, the domain-specific relevant information will be analyzed. The study consists of 4 main subsections, beginning with the theoretical part, where the necessary background information is provided and explained, and the practical part, in which the knowledge and techniques described in the theoretical part, such as PESTEL Analysis, VRIO Analysis and Logistical and Operational analysis, is applied to the company. Based on the findings in the practical part, the author of the thesis then drafts post audit recommendations, whilst acknowledging the limitations of this audit. Based on the implementation of the aforementioned recommendations, the current situation of the company will improve.
Vedoucí práce: Václav Kupec
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses